5.3.7 Problems 601 to 700

Table 5.297: Second order ode

#

ODE

Mathematica

Maple

2409

\[ {}y^{\prime \prime }-y = f \left (t \right ) \]

2410

\[ {}y^{\prime \prime }+\frac {t^{2} y}{4} = f \cos \left (t \right ) \]

2411

\[ {}y^{\prime \prime }-\frac {2 t y^{\prime }}{t^{2}+1}+\frac {2 y}{t^{2}+1} = t^{2}+1 \]

2412

\[ {}m y^{\prime \prime }+c y^{\prime }+k y = F_{0} \cos \left (\omega t \right ) \]

2431

\[ {}t^{2} y^{\prime \prime }-5 t y^{\prime }+9 y = 0 \]

2432

\[ {}t^{2} y^{\prime \prime }+5 t y^{\prime }-5 y = 0 \]

2433

\[ {}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0 \]

2434

\[ {}\left (t -1\right )^{2} y^{\prime \prime }-2 \left (t -1\right ) y^{\prime }+2 y = 0 \]

2435

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0 \]

2436

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0 \]

2437

\[ {}\left (t -2\right )^{2} y^{\prime \prime }+5 \left (t -2\right ) y^{\prime }+4 y = 0 \]

2438

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

2439

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+2 y = 0 \]

2440

\[ {}t^{2} y^{\prime \prime }-3 t y^{\prime }+4 y = 0 \]

2543

\[ {}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0 \]

2544

\[ {}y^{\prime \prime }+t y^{\prime }+y = 0 \]

2545

\[ {}y^{\prime \prime }-y = 0 \]

2546

\[ {}6 y^{\prime \prime }-7 y^{\prime }+y = 0 \]

2547

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

2548

\[ {}3 y^{\prime \prime }+6 y^{\prime }+2 y = 0 \]

2549

\[ {}y^{\prime \prime }-3 y^{\prime }-4 y = 0 \]

2550

\[ {}2 y^{\prime \prime }+y^{\prime }-10 y = 0 \]

2551

\[ {}5 y^{\prime \prime }+5 y^{\prime }-y = 0 \]

2552

\[ {}y^{\prime \prime }-6 y^{\prime }+y = 0 \]

2553

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

2554

\[ {}t^{2} y^{\prime \prime }+\alpha t y^{\prime }+\beta y = 0 \]

2555

\[ {}t^{2} y^{\prime \prime }+5 t y^{\prime }-2 y = 0 \]

2556

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

2557

\[ {}2 y^{\prime \prime }+3 y^{\prime }+4 y = 0 \]

2558

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

2559

\[ {}4 y^{\prime \prime }-y^{\prime }+y = 0 \]

2560

\[ {}y^{\prime \prime }+y^{\prime }+2 y = 0 \]

2561

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

2562

\[ {}2 y^{\prime \prime }-y^{\prime }+3 y = 0 \]

2563

\[ {}3 y^{\prime \prime }-2 y^{\prime }+4 y = 0 \]

2564

\[ {}y^{\prime \prime }+w^{2} y = 0 \]

2565

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

2566

\[ {}t^{2} y^{\prime \prime }+2 t y^{\prime }+2 y = 0 \]

2567

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

2568

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

2569

\[ {}9 y^{\prime \prime }+6 y^{\prime }+y = 0 \]

2570

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

2571

\[ {}6 y^{\prime \prime }+2 y^{\prime }+y = 0 \]

2572

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

2573

\[ {}y^{\prime \prime }-\frac {2 \left (t +1\right ) y^{\prime }}{t^{2}+2 t -1}+\frac {2 y}{t^{2}+2 t -1} = 0 \]

2574

\[ {}y^{\prime \prime }-4 t y^{\prime }+\left (4 t^{2}-2\right ) y = 0 \]

2575

\[ {}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+2 y = 0 \]

2576

\[ {}\left (t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+2 y = 0 \]

2577

\[ {}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+6 y = 0 \]

2578

\[ {}\left (2 t +1\right ) y^{\prime \prime }-4 \left (t +1\right ) y^{\prime }+4 y = 0 \]

2579

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-\frac {1}{4}\right ) y = 0 \]

2580

\[ {}t y^{\prime \prime }-\left (1+3 t \right ) y^{\prime }+3 y = 0 \]

2581

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0 \]

2582

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0 \]

2583

\[ {}y^{\prime \prime }+y = \sec \left (t \right ) \]

2584

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = t \,{\mathrm e}^{2 t} \]

2585

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = \left (t^{2}+1\right ) {\mathrm e}^{t} \]

2586

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = t \,{\mathrm e}^{3 t}+1 \]

2587

\[ {}3 y^{\prime \prime }+4 y^{\prime }+y = \sin \left (t \right ) {\mathrm e}^{-t} \]

2588

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = t^{{5}/{2}} {\mathrm e}^{-2 t} \]

2589

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sqrt {t +1} \]

2590

\[ {}y^{\prime \prime }-y = f \left (t \right ) \]

2591

\[ {}t^{2} y^{\prime \prime }-2 y = t^{2} \]

2592

\[ {}y^{\prime \prime }+p \left (t \right ) y^{\prime }+q \left (t \right ) y = t +1 \]

2593

\[ {}y^{\prime \prime }-\frac {2 t y^{\prime }}{t^{2}+1}+\frac {2 y}{t^{2}+1} = t^{2}+1 \]

2594

\[ {}y^{\prime \prime }+3 y = t^{3}-1 \]

2595

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = t \,{\mathrm e}^{\alpha t} \]

2596

\[ {}y^{\prime \prime }-y = t^{2} {\mathrm e}^{t} \]

2597

\[ {}y^{\prime \prime }+y^{\prime }+y = t^{2}+t +1 \]

2598

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-t} \]

2599

\[ {}y^{\prime \prime }+5 y^{\prime }+4 y = t^{2} {\mathrm e}^{7 t} \]

2600

\[ {}y^{\prime \prime }+4 y = t \sin \left (2 t \right ) \]

2601

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = \left (3 t^{7}-5 t^{4}\right ) {\mathrm e}^{3 t} \]

2602

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 2 \cos \left (t \right )^{2} \]

2603

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 2 \cos \left (t \right )^{2} {\mathrm e}^{t} \]

2604

\[ {}y^{\prime \prime }+y^{\prime }-6 y = \sin \left (t \right )+t \,{\mathrm e}^{2 t} \]

2605

\[ {}y^{\prime \prime }+y^{\prime }+4 y = t^{2}+\left (2 t +3\right ) \left (1+\cos \left (t \right )\right ) \]

2606

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{t}+{\mathrm e}^{2 t} \]

2607

\[ {}y^{\prime \prime }+2 y^{\prime } = 1+t^{2}+{\mathrm e}^{-2 t} \]

2608

\[ {}y^{\prime \prime }+y = \cos \left (t \right ) \cos \left (2 t \right ) \]

2609

\[ {}y^{\prime \prime }+y = \cos \left (t \right ) \cos \left (2 t \right ) \cos \left (3 t \right ) \]

2610

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = t^{{3}/{2}} {\mathrm e}^{3 t} \]

2628

\[ {}t^{2} y^{\prime \prime }+5 t y^{\prime }-5 y = 0 \]

2629

\[ {}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0 \]

2630

\[ {}\left (t -1\right )^{2} y^{\prime \prime }-2 \left (t -1\right ) y^{\prime }+2 y = 0 \]

2631

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0 \]

2632

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0 \]

2633

\[ {}\left (t -2\right )^{2} y^{\prime \prime }+5 \left (t -2\right ) y^{\prime }+4 y = 0 \]

2634

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

2635

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+2 y = 0 \]

2636

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }-2 y = 0 \]

2637

\[ {}t^{2} y^{\prime \prime }-3 t y^{\prime }+4 y = 0 \]

2671

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = {\mathrm e}^{2 t} \]

2672

\[ {}2 y^{\prime \prime }+y^{\prime }-y = {\mathrm e}^{3 t} \]

2673

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-t} \]

2674

\[ {}y^{\prime \prime }+y = t^{2} \sin \left (t \right ) \]

2675

\[ {}y^{\prime \prime }+3 y^{\prime }+7 y = \cos \left (t \right ) \]

2676

\[ {}y^{\prime \prime }+y^{\prime }+y = t^{3} \]

2678

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{-t} \]

2679

\[ {}y^{\prime \prime }+y = \sin \left (t \right ) \]